In And On Service Training Conceptual Model Based On Andragogy to Improve The Competency Of Supervisor Of Early Childhood Education Program (PAUD) - Misran Rahman; Asni Ilham (JURNAL BUNGA RAMPAI USIA EMAS, 2017)
In Gorontalo Province, the role of Supervisors of Early Childhood Education (PAUD) is not as optimal as has been expected. We stated this based on the results of interviews done by researchers to the PAUD managers and tutors, which few supervisors have obstacles in guiding tutors to manage to learn and in guiding principals to manage early childhood institutions. The problem mightcause by the improper recruitment of supervisors which was not involving the standardization, qualification, and competence of the supervisors. Consequently, it is necessary to improve the competence of PAUD supervisors by, one of them, education and training. Hence, In and On Service Training model based on andragogy presented here.The initial stage to develop this model is to provide the conceptual model. Therefore, the purpose of this early stage of research is to build the conceptual model of in and On service training based on Andragogy and its tools toimprove the competence of PAUD supervisors.The method used in this research is development research, includes: (i) theoretical and regulatory study of supervisory, no formal education, and also education and training, (ii) surveys and identification of supervisor competency profiles, (iii) construction of conceptual model by workshops, and (iv ) Model validation.The result of the model consists of (i) design of training models, tools, guides, and assessment instruments, (ii) teaching materials, (iii) supervisory evaluation tools, (iv) academic supervision tools, and (v) managerial, supervisory material.